Assessment of forage quality Among the sudangrasses, sweet and grain sorghum inbred lines at different cutting time points - Mugwanya, Muziri (AUC Knowledge Fountain, 2020)
Sorghum bicolor (L.) Moench is the world's fifth mostly cultivated cereal after wheat, corn, barley, and oats. Although originated in Ethiopia, the United States is the leading producer and exporter of grain sorghum worldwide. In Africa, it is the second most widely grown crop after corn and mainly cultivated in the arid and semi-arid regions of the continent. Its hardiness to environmental stress and low costs of production has made it a more viable forage crop for animal consumption in marginal agricultural regions. In this study, twelve sorghum varieties were evaluated for their forage quality based on their agro-morphological traits and cell wall composition. Results of the agro-morphological trait analysis showed that black-seeded Sudangrass had the lowest dry weight compared to the sweet sorghum cultivars (Sugar Drip, Rex and Ramada) and this was significant at 90 days after sowing (DAS). This was reflected on its low in vitro digestibility and thus its low forage quality. In addition, the Sudan grasses exhibited a significant decrease in their fresh and dry weights, stalk diameter, leaf width and leaf number with advancing plant maturity. This correlated with their forage quality thus the best cutting time point for the Sudan grasses was at 75 DAS. Results of fiber fraction, nutritive analysis and in vitro digestibility indicated that Sugar Drip had the highest forage quality as evident from its low lignin content, high Relative Feed Value and highest Net Energy of Lactation at and this was significant at 90 DAS. This was followed by Rex, Ramada, MN1054, white-seeded Sudangrass, GK Aron and black-seeded Sudangrass. Grain sorghum cultivars were harvested at grain maturity and results of in vitro digestibility of their cell wall components were slightly comparable to sweet sorghum. However, Sohag was significantly superior to LG35 in terms of its RFV and in vitro digestible dry matter. Single nucleotide polymorphisms (SNPs) in one of the lignin biosynthesis genes; caffeic acid 3-O-methyltransferase (COMT) were evaluated for their effect on forage quality. The detected SNPs is expected to affect protein function. No correlation was noted between the COMT SNPs and lignin content and accumulation in the studied cultivars. Likewise, the detected SNPs did not have any effect of forage quality.